Analysis of Heavy Metal Cadmium (Cd) Content on Mud Crab (Scylla sp.) at Wonorejo River Surabaya - Nanang Ardianto; Prayogo Prayogo; Adriana Monica Sahidu (Journal Omni-Akuatika, 2019)
The coastal waters of Wonorejo is part of the East Coast Surabaya which receive the brunt of watersheds (DAS) from other rivers. The main source of heavy metal wastes in the River on the downstream Wonorejo pass several industries suspected of disposing of hazardous waste. One of the main heavy metal which is a toxic element and effect on aquatic ecological systems are cadmium (Cd).Mud crab is one potential biota found in the mangrove area of Wonorejo River Surabaya can accumulate heavy metals. This research was carried out in April 2018 with sampling at three stations with time each week for three times.Analysis of heavy metals cadmium (Cd) in mud crabs (Scylla sp.), water and sediments carried out in the laboratory of nutrition of the Faculty of public health University Airlangga. Research method using observation which is channeled in the waters and farmed in Wonorejo Surabaya. Mud crab meat samples, water and sediments tested using Atomic Absoption Spectrophotometry (AAS). The results of the test concentration of heavy metals cadmium (Cd) in mud crab meat on the river Wonorejo i.e. 0.032 mg.kg-1 where the value of these levels are still below the threshold of quality raw heavy metal Cd on crustaceans i.e. 1 mg.kg-1 (SNI 7387:2009). The Cd content in water of Wonorejo river in between 0.014-0.02 ppm and on sediments between 0.234-0.416 mg/kg. Correlation of cadmium content in water with crab meat in the correlation coefficient shows of Wonorejo -0.22 (a weak correlation, a negative direction). Then, the correlation of the content of cadmium in sediments with crab meat in the correlation coefficient shows of Wonorejo 0.285 (of correlation is weak, the positive direction).